Policing and crime control in post-apartheid South Africa - Singh, Anne-Marie (Interdisciplinary research series in ethnic, gender and class relations, 2008)
Introduction -- Crime control and political authorities -- Crime control and the private security industry -- Crime control and corporate enterprises -- Crime control and community authorities -- Conclusion : coercion, crime control and governance